STUDY ON ANTI-OSTEOSARCOMA ACTIVITY OF ETHANOL EXTRACT OF VENENUM BUFONIS IN VITRO - Chen, Guangxing; Jiang, Xuefeng; Li, Jingyi; Duan, Guangjie; Yang, Liu; Zhang, Ying; Wang, Fuyou (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Venenum bufonis is the dried white secretion of the auricular and skin glands of Bufo gargarizans Cantor, or Bufo melanostictus Schneider, Bufonidae. It is used in the treatment of deep-rooted carbuncle, boils and swelling; pain in the throat, heart stroke, coma, abdominal pain, vomiting and diarrhea. The objective of this paper is to preliminarily observe the effects of ethanol extract of Venenum bufonis on growth, and proliferation of human osteosarcoma U2OS cell lines, and to provide a theoretical basis for an in-depth study of the clinical application of Venenum bufonis for osteosarcoma inhibition, with its mechanism of action. Materials and Methods: SRB assay was used to determine the effect of Venenum bufonis ethanol extract on U2OS cell line activity, and to detect its inhibitory dose-effect on osteosarcoma cells. FCM was applied to determine the effect of Venenum bufonis ethanol extract on U2OS cell apoptosis and to perform cell cycle analysis. Results: As results, different Venenum bufonis ethanol extracts showed apparent concentration-effect relationships on U2OS cell lines. FCM analysis showed that it had a U2OS apoptosis promoting effect, which increased with increasing concentration. Cell cycle analysis revealed that the Venenum bufonis ethanol extract mainly arrested U2OS in the G0/G1 phase, preventing the cells from progressing to the S phase. Conclusion: The study concluded that Venenum bufonis ethanol extract has an inhibitory effect on proliferation of osteosarcoma U2OS cells.